Perfil clínico, epidemiológico e imunológico de familiares de pacientes com leishmaniose visceral - Moraes, Juliana Lima Silva (2013)
Visceral leishmaniasis is endemic in many Brazilian states, including Sergipe. Through a cross-sectional study done with relatives of patients with visceral leishmaniasis, we determined the frequency of asymptomatic infection by Leishmania chagasi using Montenegro skin test and/or Enzyme Linked Immunosorbent Assay (ELISA). Questionnaire containing socio-demographic data, presence of signs and symptoms, physical examination of 109 subjects were analyzed. Environmental factors such as the presence of dog, chicken and wood in the residence were also investigated. Finally, the levels of cytokines Tumor Necrosis Factor (TNF)-α, Transforming Growth Factor (TGF)-β and Interleukin (IL)-1, IL-6, IL-8, IL-10 and IL-12 were measured in 59 of these individuals. The frequency of positivity was detected in 51.8% of participants, being higher in males (61.9%). Positive testes were also more common in people over 14 years (79.7%). All positive individuals were considered asymptomatic and did not return to the hospital with complaints until the end of the study, suggesting that did not progress to other clinical forms. There was no difference between the origin: capital or the state, but more positive cases occurred at the capital, confirming the growing urbanization of the disease. Environmental factors was statistically significant when analyzed presence of dog and waste wood together (p <0.05). TGF-β showed a significant difference in favor of the negative individuals (p = 0.002), while IL-10 and IL-12 were higher in people with positive tests (p = 0.024 and 0.038). Control measures should be aimed to the population of our state, who is highly exposed to the parasite.